Calculation Clearance Between Aircraft - Hartono Hartono (Institut Teknologi Dirgantara Adisutjipto, 2020)
Airport aprons, aprons, ramps, or asphalt, are areas of an airport where aircraft are parked, unloaded or loaded, refueled, or ridden. Although the use of an apron is covered by regulations, such as lighting on a vehicle, it is usually more accessible to users than a runway or taxiway. The method used is to look at the rules or regulations in force in Indonesia, namely on Peraturan Direktur Jenderal Perhubungan Udara, No : SKEP/77/VI/2005 about Persyaratan Teknis Pengoperasian Fasilitas Teknik Bandar Udara. In this study, the extent of apron needs with the ability to accommodate 2 to 3 aircraft will be calculated. If the calculation results use aircraft specifications N219 (Nurtanio) and Stemme S-15, the Clearance between aircraft ready to takeoff is 556.5 m2.